Fatigue analysis of Package Terminal Air Conditioner motor bracket under dynamic loading - Loh, S.K.; Chin, W. M.; Faris, Waleed Fekry (Elsevier, 2009)
Motor bracket has been designed as a framework to support motor and fan in air conditioning products. Vibration and fatigue of motor bracket has been continuously a concern which may lead to structural failure if the resulting vibration and stresses are severe and excessive. It is a significant study which requires in-depth investigation to understand the structural characteristics and its dynamic behavior. This paper presents and focuses on some Finite Element (FE) analyses performed such as frequency analysis to determine the structural response due to harmonic excitation over a frequency range. The resonant frequency can be predicted based on the responses in frequency domain. Besides that, the static and dynamic vibration analyses give the maximum structural stress condition under static loading and dynamic condition. The predicted maximum stresses are compared with inherent material yield strength. The plastic deformation is not covered in the study as only elastic property is defined. A fatigue failure prediction of the current P-TAC motor bracket using FE simulation and fatigue failure criteria approach has also been studied. The dynamic stress curve giving mean stress and alternating stress has been applied in the established fatigue failure criteria such as Yield Criteria and Fracture Criteria to predict the possibility of fatigue occurrence. This approach is considered a conservative prediction approach to prevent structural fatigue which is best suited and safe for certain design applications. In the effort to strengthen the motor bracket, different modifications of the motor bracket geometry have been investigated and the comparison of results of each analysis is presented. The rib support, edge radius and thickness have been modified and added to examine the effect to the overall static and dynamic behavior. It is found that the rib-support addition and the increase of edge radius can effectively improve the structural performance based on the analyses involved.